Maps of utopia H.G. Wells, modernity, and the end of culture - James, Simon J. (Oxford : Oxford University Press, 2012)
This is a study of the literary theories of H.G. Wells, the founding father of English science fiction and once the most widely read writer in the world. It explores his career, during which he produced popular science, educational theory, history politics, and prophecy, as well as realist, experimental, and science fiction.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Wells, H. G. -- 1866-1946 -- Criticism and interpretation; Wells, H. G. -- 1866-1946 -- Aesthetics